Analytical Characterization of Medium Molecular Weight Chitosan from Pink Shrimp (Metapenaeus dobsoni) Shells - Ammara Tooba Akbar; Mahnaz Ahmad; Rashida Rahmat Zohra; Raheela Rahmat Zohra; Ahmad Khan; Muhammad Atiq Ur Rehman; Mohamed Abbas (Pakistan Journal of Analytical & Environmental Chemistry)
Seafood is widely consumed across the globe and serves as a vital source of essential nutrients. However, the processing of seafood generates significant amounts of waste, including shells and scales, which hold potential for the production of valuable byproducts. This study presents an efficient method for synthesizing high-quality chitosan from Pink shrimp (Metapenaeus dobsoni) shells. The extraction process involves a novel two-step purification of chitin, followed by an energy-saving freeze-pump-out-thaw (FPT) cycle and optimized deacetylation to obtain chitosan. Physicochemical characterization revealed that the chitosan has an average molecular weight (Mv) of 620 kDa and is soluble in 1% acetic acid. Scanning electron microscopy (SEM) confirmed the conformation of the synthesized chitosan. The degree of deacetylation was determined to be 97.2% using Fourier-transform infrared spectroscopy (FTIR), while the crystallinity index (Icr) was calculated at 69% via powdered X-ray diffraction (XRD). The findings demonstrated that the chitosan extracted from this crustacean source possesses unique physical and chemical properties, making it highly suitable for applications in biomedical fields and food packaging.